Operational experiences of municipal heating plants with biomass-fired ORC cogeneration units. (1st February 2019) - Kalina, Jacek; Świerzewski, Mateusz; Strzałka, Rafał
Highlights: Long-term operational experiences from two ORC cogeneration plants are reported. Variability of operational parameters including biomass quality is explained in detail. Key performance indicators are discussed. Current macroeconomic and project profitability issues are presented. SWOT analysis of the technology has been performed. Abstract: This paper reports on operational experiences and performance of two municipal heating plants that were converted into cogeneration plants by the installation of biomass-fired modules based on the Organic Rankine Cycle technology (ORC). Two different plants of this type are presented. The text provides a review and discussion of critical issues related to implementation of the technology. Similarities, differences and operational characteristics are substantiated by the analysis of long-term measurement data. Particular attention is paid to variability of operational parameters, problems with determination of performance indicators, equipment characteristics, system sizing and its integration with existing heating plants. A special focus is put on profitability of investment projects under variable economic conditions. Finally, the technology is evaluated using Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. The text fills the gap between the theoretical knowledge and required practical know-how. It also indicates areas of possible improvements and helps technological risk analysis in the future investment projects.